The Effects of Self-Assessment System and Tax Collection Letter on Value Added Tax Revenue at the Bandung Cibeunying Primary Tax Service Office - Purnamasari, Dyah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out how the effect of the self-assessment system and tax collection on tax-added tax revenue at the Bandung Cibeunying Primary Tax Service Office. The object of this research is a self-assessment system and tax collection letter on valued tax revenue. The research methods used in this study are descriptive and verification methods. Data analysis used in this study is multiple linear regression analysis at a significance level of 5%. Research results show that self-assessment systems and tax collection letters have an effect on value-added tax revenue. So the higher the self-assessment system and tax collection letter, the more value-added tax revenue.